Control Algorithm of Energy Storage System Based on Virtual Synchronous Generator - Suvorov Aleksey; Askarov Alisher; Rudnik Vladimir (E3S Web of Conferences)
Frequency control is one of the most important tasks in electric power systems. However, as a result of the ongoing introduction into modern power systems of inertia-free generating facilities based on power converters, mainly renewable energy sources, this task is becoming more complex. This specificity is especially severe in microgrids, which are characterized by significant frequency changes. An effective way to solve such a problem is the use of energy storage systems (ESS) with grid-forming power converters. For this purpose, the paper develops a new structure of the control algorithm based on a current-controlled virtual synchronous generator (CC-VSG), in which the damping of oscillations is implemented via a feedforward controller. Also, a proportional-integral control loop is added to the structure of the CC-VSG to control the state of charge of the ESS. A methodology based on the separation of bandwidths of different control loops is proposed for tuning the CC-VSG. To confirm the obtained results, time-domain simulation of the microgrid with ESS using the PSCAD software was performed.